The Description of Scenes Over Time and Space - Uhr, Leonard (University of Wisconsin-Madison Department of Computer Sciences, 1973)
This paper explores techniques for pattern recognition and description of more than one object, where objects extend over time as well as over space. Three major interrelated issues are examined: A. Describing, as opposed to simple naming; B. Time, and the way a system can build up a short-term perceptual memory to handle and make use of changing information; C. Glancing around, in order to recognize and describe. Two actual computer programs are presented, to make clear exactly what the issues are and how they are handled, and to make comparisons possible. Program DESCRIBE-1 uses configurational characterizers, and describes by outputting several highly-implied objects. Program DESCRIBE-2 handles inputs that extend over time. It glances about and gives structural descriptions of the parts of objects. A number of variants are examined, to explore how a program can describe with more variety. Descriptors: Scene Analysis, Describing, Pattern Naming, Time, Flexible Pattern Recognition